The Effectiveness of the Internet of Things in Increasing Students Creativity - Enos Lolang; Suyahman Suyahman; Made Darmiati; Heru Widoyo; Dewi Maharani Rachmaningsih; Tomi Apra Santosa (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effectiveness of the Internet of Things to increase student creativity. This type of research is a meta-analysis. The research data came from searching the databases of Google Scholar, ScienceDirect, Researchgate and Springer. The inclusion criteria in the research are research published in international journals or proceedings indexed by Scopus, Wos and Sinta, Research related to the Internet of Things to increase student creativity, research must be published 2020-2024, and research has complete data to calculate the value of effect size. Statistical analysis in research with JSAP application .0.8.5. The results of the study concluded that the implementation of the Internet of Things (IoT) had a significant effect on student creativity with a very high summary effect size (rRE = 1.117) in the effect size category. These findings explain that the Internet of Things is effective in helping students increase their learning creativity in schools.